PERAN GURU SOSIOLOGI MENINGKATKAN MOTIVASI BELAJAR SISWA SETELAH PEMBELAJARAN DARING DI SMA NEGERI 1 X KOTO KABUPATEN TANAH DATAR - Putri, Neolita Glasi; Rahayu, Sri; Wahyuni, Yanti Sri (Universitas Tanjungpura, 2022)
Changes in the teaching and learning process from online to offline have an effect on students' learning motivation. So this also has an impact on the lack of students' understanding of the learning material. In this case, of course, the teacher's role is needed in increasing student learning motivation, so that students can understand the learning material provided. The purpose of this study was to describe the role of sociology teachers in increasing students' learning motivation after online learning. The theory used in this study is the Behavioristic theory proposed by B.F Skinner. The research was conducted at SMAN 1 X Koto Nagari Aie Angek, X Koto District, Tanah Datar Regency, West Sumatra. This study uses qualitative research methods with descriptive research type. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, in-depth interviews, and document studies. Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that in increasing students' learning motivation the teacher acted as a motivator, where the things the teacher did were to be open, arouse students' interest, give gifts, give reprimands or punishments, and give assessments to students.